1992
DOI: 10.1210/en.130.3.1424
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression of insulin-like growth factors (IGFs), the type 1 IGF receptor, and IGF-binding proteins in dexamethasone-induced fetal growth retardation

Abstract: Altered gene expression and/or actions of the insulin-like growth factors (IGFs) have been implicated in the mediation of both pre- and postnatal growth retardation secondary to glucocorticoid excess. To investigate this possibility, we assessed the gene expression of the IGFs, the type I IGF receptor, and IGF-binding proteins (IGFBPs) in 20-day gestation liver and lung of growth-retarded fetuses whose mothers were treated with dexamethasone (DXM; 100 micrograms, ip, daily) on gestation days 15-19 (gestation =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
39
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 0 publications
6
39
0
Order By: Relevance
“…Exogenous glucocorticoids have been reported to reduce both circulating IGF-I concentrations and tissue IGF-I mRNA levels (Luo & Murphy 1989, Jensen et al 2002. However, other studies have reported no effect of glucocorticoids on circulating IGF-I concentrations or tissue IGF-I mRNA levels, but an increase in IGFBP expression, suggesting that IGF bioavailability may be decreased (Mosier et al 1987, Price et al 1992.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exogenous glucocorticoids have been reported to reduce both circulating IGF-I concentrations and tissue IGF-I mRNA levels (Luo & Murphy 1989, Jensen et al 2002. However, other studies have reported no effect of glucocorticoids on circulating IGF-I concentrations or tissue IGF-I mRNA levels, but an increase in IGFBP expression, suggesting that IGF bioavailability may be decreased (Mosier et al 1987, Price et al 1992.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies of growth restriction induced by different means in different species have reported a 1·7-to 10-fold upregulation of hepatic IGFBP-1 and/or BP-2 expression; for example, prolonged hypoxia in sheep (McLellan et al 1992), maternal fasting (Straus et al 1991), dexamethasone treatment (Price et al 1992) and being small for gestational age in the rat (Unterman et al 1990) and uterine artery ligation in the guinea pig (Carter et al 2005). We found a 1·7-fold increase in IGFBP-1 expression in liver in the saline-treated fetuses but this was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Glucose intolerance in adult rats exposed to maternal dexamethasone in utero has been associated with elevations in hepatic glucocorticoid receptors (GR) and glucocorticoid-sensitive enzymes involved in gluconeogenesis such as phosphoenol-pyruvate carboxykinase (PEPCK) mRNA levels (Nyirenda et al 1998, Saegusa et al 1999. In rats, administration of maternal carbenoxolone, an inhibitor of a placental 11 -hydroxysteroid dehydrogenase (11 HSD) thus permitting increased passage of maternal glucocorticoids to the fetus (Whorwood et al 1993), has been shown to reduce birth weight in a manner similar to that observed with dexamethasone treatment (Price et al 1992, Levitt et al 1996, Nyirenda et al 1998. Moreover, adult male offspring demonstrated altered glucose tolerance indicated by higher fasting glucose levels and elevated glucose and insulin responses to a glucose challenge.…”
Section: Introductionmentioning
confidence: 96%
“…In experimental animal models, high doses of GCs also have a growthsuppressive effect on longitudinal bone growth (Price et al 1992, Leili & Scanes 1998, Rooman et al 1999, Silvestrini et al 2000. GCs have been shown to act locally to inhibit longitudinal growth, suggesting a local mechanism within the growth plate (Baron et al 1992, Silvestrini et al 2000.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, GCs regulate the expression of IGFs (Jux et al 1998) and IGFBPs (Koedam et al 2000) in chondrocytes in vitro. Few data are available, however, concerning the regulation by GCs in vivo (Price et al 1992) and it has been reported that serum levels of IGF axis components provide little insight into the mechanisms of GC-induced growth retardation and the possible involvement of the IGF axis components therein (Ward et al 1999). Therefore, in order to elucidate the possible involvement of IGF axis components in GC-induced growth retardation, it is important to study locally produced IGFs and IGFBPs and their regulation by GCs in the growth plate.…”
Section: Introductionmentioning
confidence: 99%